Dakwah Salafi Berbasis Kearifan Lokal Mingkabau: Studi Program Siaran Suluah Minang di Surau TV - Tomi Hendra, (Jurnal Komunikasi Islam, 2022)
This study aims to examine how Salafi da'wah TV, Surau TV, has utilised local wisdom for proselytising. Using a descriptive qualitative approach through field research, the findings illustrate that the local tradition-based Salafi da'wah represented in the Suluah Minang program presents a different face of puritan Islam. The Salafi group, which has been considered to understand Islam textually and reject local wisdom, turns out to consider the existence of local culture as long as it is not ad odd with the principle of monotheism (tauhid). According to audiences, although Surau TV promotes a Salafi perspective, they do not reject the teachings presented on Surau TV, the Suluah Minang program in particular. This is because the themes discussed in this da'wah program do not directly offend religious groups, but it only explains cultural phenomena that are considered to be conflict with religious values through the arguments of the Qur'an and sunnah.